A self-conscious art : Patrick Modiano's postmodern fictions - Kawakami, Akane (Modern French writers, 2000)
A Self-Conscious Art is the first full-length study in English to attempt to deal with the formal complexities of Modiano?s work, by reading?against the grain? of his self-professed ingenuousness. A detailed examination of his narratives shows the deeply postmodern nature of his writing. Parodying precursors such as Proust or the nouveau romanciers, his narratives are built around a profound lack of faith in the ability of writing to retrieve the past through memory, and this failure is acknowledged in the discreet playfulness that characterises his novels. This book is a timely introduction.